Profil Kebugaran Fisik Atlet Anggar Kursi Roda Elit: Studi Deskriptif Komponen Biomotorik - Rahadi, Ikrar Setia; Tommoliyus, Tommoliyus; Sukamti, Endang Rini; Maslikah, Uzizatun (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2026)
Abstract Wheelchair fencing is an adaptive sport that emphasizes the use of upper limbs in a static sitting position, and to date, there is still relatively limited study examining its physical condition profile comprehensively. This study aims to describe the physical condition profile of elite wheelchair fencing elite athletes based on the main biomotor components. The study method used is descriptive quantitative with a cross-sectional approach. The study subjects consisted of 8 athletes, including 5 male athletes and 3 female athletes. Physical condition measurements included shoulder flexibility, shoulder muscle endurance, right and left hand grip strength, hand reaction speed, and aerobic capacity (Aeerobic capacity). Data analysis was performed using descriptive statistics in the form of average values. The results showed that Aeerobic capacity values were 43.5 ml/kg/minute in male athletes and 36.1 ml/kg/minute in female athletes. Shoulder flexibility values were 112 cm in male athletes and 63 cm in female athletes, and shoulder endurance was 56 seconds in male athletes and 17.75 seconds in female athletes. In addition, the right hand grip strength value was 44.3 kg in male athletes and 17.1 kg in female athletes, and the left hand was 24.3 kg in male athletes and 18.1 kg in female athletes. The hand reaction value was 150 ms in male athletes and 175 ms in female athletes. The conclusion of the study shows that the physical condition profile of elite wheelchair fencers is at a varying level between biomotor components, with aerobic capacity and grip strength being relatively better than flexibility and reaction speed. These results can be used as a basis for developing a more specific training program and in accordance with the demands of the sport of wheelchair fencing. Keywords: biomotor, physical fitnes, wheelchair fencing.